Through Mintzberg's glasses: a fresh look at the organization of ministries of health - Jean-Pierre Unger; Jean Macq; François Bredo; Marleen Boelaert (The World Health Organization, 2000)
In 1987, district health care policies were officially adopted by a majority of developing countries. Many operational problems constraining implementation of such policies have subsequently been identified, most of which are attributable to well-known characteristics of less developed countries. However, the policy of operational and administrative decentralization has often been critically obstructed by inappropriate organizational structures in ministries of health. By applying Mintzberg's analytical framework to several ministries of health, we identify structural deficiencies that make systems unfit to match their policy environment and yield the expected outcomes of functional and decentralized services. We propose a typology likely to elicit strategies for decentralizing health care administration. Our analysis is based on the following steps: - a description of Mintzberg's concepts of organizational structure, generic components (strategic apex, technostructure, supporting structure, middle line, operational core) and functions (horizontal and vertical integration, liaison devices, vertical and horizontal decentralization) applied to health systems; - a discussion of divisionalized adhocracy as a suitable configuration for health organizations with a need for a high degree of regional autonomy, community participation, medical staff initiative, action research and operational research, and continuous evaluation; - a discussion of the organizational features of a number of health ministry systems and a consideration of strategies for transforming configurations towards divisionalized adhocracy.